2018
DOI: 10.4067/s0718-22442018000100155
|View full text |Cite
|
Sign up to set email alerts
|

Interacciones bioculturales del pueblo yagán con las macroalgas y moluscos: Una aproximación desde la filosofía ambiental de campo

Abstract: The coastal areas of the Magellan ecoregion host considerable diversity of macroalgae and mollusks. Indigenous peoples, such as the Yaghan, have developed biocultural interactions with austral coastal ecosystems. This study is an interdisciplinary ecological, ethnoecological and philosophical analysis. It applies the conceptual framework of biocultural ethics to characterize the intertidal habitat within the biocultural context of the Yaghan people. This is done through the composition of inhabitants, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 23 publications
1
20
1
6
Order By: Relevance
“…The multivariate analysis showed differences in the assemblage composition of micro and macroalgae between the two localities at each intertidal level and time. This dynamics of macroalgae assemblages in the channels and fjords of the Magellan Ecoregion was also observed by Ojeda (2013) , who observed that the macroalgae assemblages do not present a general spatial structuring pattern, and there may even be differences in the structure of macroalgae assemblages between sites for similar intertidal levels within a same Bay ( Ojeda 2013 ). This author also found that the macroalgae assemblages temporally presented a decrease in wet biomass in winter periods and a considerable increase in summer, showing the marked temporal dynamics of the macroalgae assemblages.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…The multivariate analysis showed differences in the assemblage composition of micro and macroalgae between the two localities at each intertidal level and time. This dynamics of macroalgae assemblages in the channels and fjords of the Magellan Ecoregion was also observed by Ojeda (2013) , who observed that the macroalgae assemblages do not present a general spatial structuring pattern, and there may even be differences in the structure of macroalgae assemblages between sites for similar intertidal levels within a same Bay ( Ojeda 2013 ). This author also found that the macroalgae assemblages temporally presented a decrease in wet biomass in winter periods and a considerable increase in summer, showing the marked temporal dynamics of the macroalgae assemblages.…”
Section: Discussionsupporting
confidence: 68%
“…These results suggest indetectable general pattern in the vertical zonation of micro- and macroalgae assemblages in these two localities (this study). In the channels and fjords of the Magellan Ecoregion, it has been described that the local environmental heterogeneity likely plays a role in structuring ecological assemblages and communities in Sub-Antarctic marine channels ( Ríos et al 2007 , Aldea et al 2011 , Ojeda 2013 , Ojeda et al 2014 ). Finally, our data suggest an absence of a vertical pattern zonation between the two sites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Jaime Ojeda y colaboradores (Ojeda et al 2018) abordan la noción de valor intrínseco y su complementariedad con la noción de valor instrumental, proponiendo superar la dicotomía entre ambos valores, en el contexto del estudio sobre los moluscos de los canales del Cabo de Hornos y su importancia en la cosmovisión yagán. Estos autores afirman que las distintas especies de moluscos poseen para la cultura yagán tanto un valor instrumental como un valor intrínseco.…”
Section: El Valor éTico En La Cultura Yagánunclassified